Whole‐body magnetic resonance imaging plus serological follow‐up for early identification of progression in smouldering myeloma patients to prevent development of end‐organ damage - Wennmann, Markus; Goldschmidt, Hartmut; Mosebach, Jennifer; Hielscher, Thomas; Bäuerle, Tobias; Komljenovic, Dorde; McCarthy, Philip L.; Merz, Maximilian; Schlemmer, Heinz‐Peter; Raab, Marc‐Steffen; Sauer, Sandra; Delorme, Stefan; et al. (British journal of haematology, 2022)
Summary The definition of multiple myeloma (MM) was updated in 2014, with the intent to enable earlier treatment and thereby avoid appearance of end‐organ damage at progression from smouldering multiple myeloma (SMM) to MM. The purpose of this study was to investigate to which extent the development of end‐organ damage at progression to MM was reduced under the updated guidelines. In this prospective observational cohort study (ClinicalTrials.gov Identifier: NCT01374412), between 2014 and 2020, 96 SMM patients prospectively underwent whole‐body magnetic resonance imaging (wb‐MRI) and serological follow‐up at baseline and every 6 months thereafter. A total of 22 patients progressed into MM during follow‐up, of which seven (32%) showed SLiM‐criteria only but no end‐organ damage. Four (57%) of the seven patients who progressed by SLiM‐criteria only progressed with >1 focal lesion (FL) or a growing FL, and three (43%) due to serum free light‐chain‐ratio ≥100. Fifteen (68%) out of 22 patients who progressed still suffered from end‐organ damage at progression. The updated disease definition reduced the proportion of SMM patients suffering from end‐organ damage at progression to MM by one third. wb‐MRI is an important tool for detection of SMM patients who progress to MM without end‐organ damage.